2021
DOI: 10.1186/s12891-021-04660-4
|View full text |Cite
|
Sign up to set email alerts
|

CT-based and morphological comparison of glenoid inclination and version angles and mineralisation distribution in human body donors

Abstract: Background For optimal prosthetic anchoring in omarthritis surgery, a differentiated knowledge on the mineralisation distribution of the glenoid is important. However, database on the mineralisation of diseased joints and potential relations with glenoid angles is limited. Methods Shoulder specimens from ten female and nine male body donors with an average age of 81.5 years were investigated. Using 3D-CT-multiplanar reconstruction, glenoid inclinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The normal mean glenoid inclination was approximately 10°superior when the scapular trigonum is used as a medial landmark 24 . Recently, there has been increasing evidence that more superior glenoid inclination both preoperatively and postoperatively can result in tendon strain and attritional damage progressing to RCT 8,23,25 .…”
Section: Glenoid Inclinationmentioning
confidence: 99%
“…The normal mean glenoid inclination was approximately 10°superior when the scapular trigonum is used as a medial landmark 24 . Recently, there has been increasing evidence that more superior glenoid inclination both preoperatively and postoperatively can result in tendon strain and attritional damage progressing to RCT 8,23,25 .…”
Section: Glenoid Inclinationmentioning
confidence: 99%
“…In contrast to conventional methods of CT densitometry, which measure absolute values for bone density in large areas, CT-OAM can demonstrate the relative distribution over the entire surface using a false-color diagram. This technique allows for the detection of differences in relative distribution [15][16][17][18]. CT-OAM was evaluated using Analyze 14.0 (Analyze Direct Inc., Overland Park, KS, USA).…”
Section: Computed Tomography Osteoabsorptiometrymentioning
confidence: 99%
“…Headaches occurred together with the development of subjective bony swellings on the skull. History revealed subtotal gastrectomy with T1 lymph node dissection because of a malignant neoplasm (stage pT1(a)N0M0; R0; G3; L0; V0, UICC Ia) three years earlier, which was in ongoing remission after the clinical screening with additional gastroscopy, the first CT, and another 18 F-FDG-PET-CT during follow-up.…”
Section: Patient's Assessment and Follow-up With Multimodal Diagnosticsmentioning
confidence: 99%
“…The glenoid version and subchondral mineralization variability are affected by gender, ethnicity, shoulder dominance, age, and genetics. 5 , 19 , 24 With respect to genetics, Landau and Hoenecke reported that there is no genetic relationship between the scapular blade and vault, contributing to an extremely variable osseous interaction which is not a characteristic of most other bones. 15 This large variability in glenoid anatomy suggests that there might not be an optimal fixed position to place the glenoid, but instead, it may depend on individual characteristics and regional anatomy.…”
mentioning
confidence: 99%